Controlling hopf bifurcations: Discrete-time systems. Issue 1 (2000) - Chen, Guanrong; Fang, Jin-quing; Hong, Yiguang; Qin, Huashu
Abstract : Bifurcation control has attracted increasing attention in recent years. A simple and unified state-feedback methodology is developed in this paper for Hopf bifurcation control for discrete-time systems. The control task can be either shifting an existing Hopf bifurcation or creating a new Hopf bifurcation. Some computer simulations are included to illustrate the methodology and to verify the theoretical results.